PRIMARY PULMONARY HODGKIN’S LYMPHOMA: A CASE OF DIAGNOSTIC COMPLEXITY AND TREATMENT RESISTANCE - Radosław Pastuszek; Magdalena Rosiewicz; Karolina Bieńkowska; Aleksandra Pastuszek; Anita Janda; Sylwia Bartolik; Marcin Durowicz; Iwona Górnicka; Jan Drzymała; Urszula Kierepka (International Journal of Innovative Technologies in Social Science, 2025)
Primary pulmonary Hodgkin’s lymphoma (PPHL) arises from the lymphoid tissue of the alveolar mucosa or peribronchial lymph nodes. PPHL is extremely rare, representing only 1.5–2.4% of all cases of primary pulmonary lymphoma.[1] Its rarity and nonspecific presentation often lead to diagnostic delays. Symptoms such as cough, fatigue, or chest discomfort mimic other pulmonary diseases, complicating clinical evaluation. Here, we present a case of PPHL initially misdiagnosed as granulomatosis with polyangiitis due to overlapping clinical and histopathological findings. This case emphasizes the importance of a multidisciplinary approach and highlights the critical role of thorough histopathological analysis in establishing an accurate diagnosis.